Theoretical Organization of Motivations to Attend First Aid Education: Scoping Review (International Journal of First Aid Education)
First Aid Education serves the public’s health to prepare for and respond to acute illness and injuries and to return people  to  health.    Understanding  motivations  for  people  to  participate  in  education  opportunities  would  help organizations contextualize learners’ expectations and be used to increase the percentage of the public trained to  respond.    Using  PRISMA  guidelines,  we  identified  existing  literature  on  individual  and/or  population motivations  to  participate  first  aid  education  and  motivational  factors  to  seek  education,  information,  and training to prepare to respond to emergencies from observational studies. The  results  however  did  not  lend  to  a  cohesive  body  in  which  metanalysis  could  be  performed.  We  present  a scoping review of literature mapped to current social and psychological theories for context and use in developing or promoting first aid education. We identified three smaller experimental studies and no large experimental or population-based studies.  Two observational or retrospective studies and eight descriptive studies rounded out the literature that included motivation to attend.  Motivations to participate in first aid education are not well described  in  the  literature  in  terms  of  magnitude  or  generalizability.    Those  identified  do  fit  into  behavioral theories, as applied in the Social-Ecological and Transtheoretical models for the benefit individual educators and training organizations. Linking theory to motivations ideally helps develop future research in the field from psychological and sociological perspectives.  Practically, there is opportunity for better research connection between education organizations who can “require” training for occupational or educational purposes to increase awareness and opportunity for first aid education.   Public health educators can also link first aid education to other public health topics or vice versa to weave in community motivations for competencies to build resilience in personal or public emergencies.